Fetal sex and the circulating renin–angiotensin system during early gestation in women who later develop preeclampsia or gestational hypertension - Sykes, S D; Pringle, K G; Zhou, A; Dekker, G A; Roberts, C T; Lumbers, E R (Journal of human hypertension, 2014)
There are fetal sex-specific differences in the balance between angiotensin (Ang) II and Ang-(1–7) in the maternal circulation during pregnancy. To determine whether at 15 weeks’ gestation plasma levels of Ang II and Ang-(1–7), as well as levels of prorenin and Ang-converting enzyme (ACE), predicted the development of gestational hypertension (GH) or preeclampsia (PreE) and were associated with estimates of fetal and maternal health, women who later developed GH ( n =50) or PreE ( n =50) were compared with body mass index-matched controls ( n =100). Women who subsequently developed PreE or GH had increased Ang-(1–7) levels at 15 weeks’ gestation compared with women with normal pregnancies. When separated by fetal sex, this difference was seen only in women carrying a female fetus. Prorenin and ACE concentrations were not useful biomarkers for the prediction of either PreE or GH at 15 weeks’ gestation. Women with a male fetus who developed PreE and women who subsequently developed GH had increased blood pressures at 15 weeks’ gestation compared with women with normal pregnancies, suggesting that these women were on an early trajectory for the development of hypertension. We propose that measurement of Ang-(1–7) during early gestation could be useful in predicting, those women who will go on to develop new-onset hypertension in pregnancy.